Cross-cultural Analysis of Politeness Language and the Cultural and Historical Reasons - Wang, Youran (Transactions on Social Science, Education and Humanities Research, 2024)
As a manifestation of human social nature in speech, politeness is vital to the development and upkeep of social relationships. People may choose to communicate the same thoughts in speech in a less direct or more oblique manner as a courtesy to both communication parties. Accordingly, politeness is a crucial field in pragmatic linguistics. The linguistic expressions of courteous language, politeness as a conflict avoidance strategy and socially indexed disparities, parameters influencing the form and function of politeness, and the impact of language type are among the subjects that researchers are presently concentrating on. The features of polite language and its origins in cross-cultural comparisons have, however, received little attention in studies. Therefore, this paper focuses on the differences and similarities in polite languages in English, French, Chinese, and Japanese, and aims to seek the reason behind using polite languages in different cultures. This study concludes that a nation’s history and culture may both impact that nation’s language as well as other nations’ languages.